2014
DOI: 10.1103/physreve.90.052817
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic spreading and risk perception in multiplex networks: A self-organized percolation method

Abstract: In this paper we study the interplay between epidemic spreading and risk perception on multiplex networks. The basic idea is that the effective infection probability is affected by the perception of the risk of being infected, which we assume to be related to the fraction of infected neighbors, as introduced by Bagnoli et al. [Phys. Rev. E 76, 061904 (2007)PLEEE81539-375510.1103/PhysRevE.76.061904]. We rederive previous results using a self-organized method that automatically gives the percolation threshold in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 23 publications
(23 reference statements)
2
53
0
1
Order By: Relevance
“…Others model populations as multiplex networks where the disease spreads over one layer and awareness spreads over another [7]. The influence of the perception of risk on the probability of infection also has been studied [8]. Several recent studies have shown how information spreads in complex networks [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Others model populations as multiplex networks where the disease spreads over one layer and awareness spreads over another [7]. The influence of the perception of risk on the probability of infection also has been studied [8]. Several recent studies have shown how information spreads in complex networks [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…When gauging infection risk, individuals may consider global information (e.g., from news media) or local first-hand encounters with disease (e.g., infected acquaintances, friends or family members) [30,31]. While traditional compartmental models assume homogeneity in both epidemiological risks and intervention benefits, network-based models provide a tractable framework for studying the complex interplay between contact networks, intervention decision making and disease transmission [34,[45][46][47][48][49][50][51].Here, we investigate the epidemiological impacts of different decision paradigms using a network-based SIR epidemic model, in which individuals also make vaccination or social distancing choices based on their perceived epidemiological risks. Depending on the decision model, they estimate either overall disease prevalence, their number of infected social contacts, or their fraction of infected social contacts.…”
mentioning
confidence: 99%
“…Simulation studies often use networks based on the free-scale model proposed by Barabasi-Albert (BA) [35], small world model proposed by Watts-Strogatz (WS) [36] and random graph model introduced by Erdos-Renyi (ER) [37]. For example [38] used WS, ER and BA synthetic networks for modeling interacting processes, [12] analyzed the role of structures of ER, BA, and WS networks on campaign performance, [39] proposed a framework to analyze multiple spreading processes and verified it with the use of BA networks, [40] used WS networks for cooperative epidemic modeling.…”
Section: Methodsmentioning
confidence: 99%